2016
DOI: 10.1016/j.cellsig.2016.08.014
|View full text |Cite
|
Sign up to set email alerts
|

E3 ubiquitin ligase NKLAM ubiquitinates STAT1 and positively regulates STAT1-mediated transcriptional activity

Abstract: Signal transducer and activator of transcription 1 (STAT1) is critically important for the transcription of a large number of immunologically relevant genes. In macrophages, interferon gamma (IFNγ) signal transduction occurs via the JAK/STAT pathway and ends with the transcription of a number of genes necessary for a successful host immune response. The predominant mechanism of regulation of STAT1 is phosphorylation; however, there is a growing body of evidence that demonstrates STAT1 is also regulated by ubiq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 43 publications
3
25
0
Order By: Relevance
“…More recent research from our laboratory demonstrated that NKLAM associates with STAT1 and mediates its K63-linked ubiquitination [ 8 ]. We have also shown that NKLAM plays significant role in facilitating the binding of STAT1 to consensus binding sites (GAS; gamma activated sites) within the promoter region of iNOS.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…More recent research from our laboratory demonstrated that NKLAM associates with STAT1 and mediates its K63-linked ubiquitination [ 8 ]. We have also shown that NKLAM plays significant role in facilitating the binding of STAT1 to consensus binding sites (GAS; gamma activated sites) within the promoter region of iNOS.…”
Section: Introductionmentioning
confidence: 99%
“…We have also shown that NKLAM plays significant role in facilitating the binding of STAT1 to consensus binding sites (GAS; gamma activated sites) within the promoter region of iNOS. Without NKLAM, IFNγ-stimulated NKLAM-KO macrophages express significantly less iNOS than wild type (WT) macrophages [ 8 ]. In response to bacteria or bacterial products, STAT1 is phosphorylated on tyrosine 701, dimerizes and translocates to the nucleus where it is involved in the transcription of many immunologically important genes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…RNF19B is a Ring finger protein family of E3 ligases, which interacts with E2 conjugating enzyme(s) and substrates, facilitating the transfer of an activated ubiquitin to the substrate [29,30]. RING finger E3 ligases have a RING structure that is involved in ubiquitinating its substrate.…”
Section: Rnf19b Is a Candidate In F508del Degradationmentioning
confidence: 99%
“…When we plotted signal for 315 H3K27me3 at ± 3 kb flanking BLIMP1 peaks, only a small level of enrichment was 316 observed ( Fig 4B). However, when we assigned the peaks from the respective 317 experiments to genes, a significant overlap of 261 genes emerged between BLIMP1 318 and H3K27me3 in RP cells ( Fig 4C), including B-cell genes PIK3CD and POU2F2 319 (OCT2), the STAT1 activator RNF19B (NKLAM) (Lawrence & Kornbluth, 2016), and 320 the cell-growth inhibitor NUB1 ( Fig 4D). 321…”
mentioning
confidence: 99%